Audit expectation gap – A perceção da gestão de topo, stakeholders e do público - Moreira, Ana Isabel da Silva Dias (2021)
The main focus of this study is to explore society's view of an auditor's work. In other words, we intend to understand if there is a "gap" between what society expects the auditor to achieve and what the auditor can and should reasonably accomplish. We considered that, since this term is universal and present in society in general, it would be interesting to address it to professionals in the area but also to professionals who do not have a background in finance. We started the literature review by exploring the term "audit expectation gap" and aimed to get a wide range of opinions through scientific and academic articles, books, web pages, magazines, and newspapers. This led to questions that were further explored through the quantitative method (use of a questionnaire) as we felt this was the most appropriate method for the purpose. This questionnaire was spread among auditing students, auditing and accounting professionals, financial directors, and professionals from several areas, where it was possible to connect the concepts, statements, and results obtained by the authors studied in the literature review with the results obtained in this dissertation. As it was found in the literature review, it was a unanimous opinion that there is effectively a difference between the functions that the auditor should perform and what the company expects him to perform, also, with this study, through the sample obtained, we shared the same opinion. It should be noted that, although we effectively agree that there is a difference between what the company expects the auditor to do and what he has to do, we found that the company in general knows the functions attributed, in general, to an auditor, however, it adds other functions that are not of its exclusive or primary competence.